Lower limb stiffness testing in athletic performance: a critical review - Maloney, S. J.; Fletcher, I. M. (Sports Biomechanics, 2021)
Stiffness describes the resistance of a body to deformation. In regard to athletic performance, a stiffer leg-spring would be expected to augment performance by increasing utilisation of elastic energy. Two-dimensional spring-mass and torsional spring models can be applied to model whole-body (vertical and/or leg stiffness) and joint stiffness. Various tasks have been used to characterise stiffness, including hopping, gait, jumping, sledge ergometry and change of direction tasks. Appropriate levels of reliability have been reported in most tasks, although they vary between investigations. Vertical stiffness has demonstrated the strongest reliability across tasks and may be more sensitive to changes in high-velocity running performance than leg stiffness. Joint stiffness demonstrates the weakest reliability, with ankle stiffness more reliable than knee stiffness. Determination of stiffness has typically necessitated force plate analyses; however, validated field-based equations permit determination of whole-body stiffness without force plates. Vertical, leg and joint stiffness measures have all demonstrated relationships with performance measures. Greater stiffness is typically demonstrated with increasing intensity (i.e., running velocity or hopping frequency). Greater stiffness is observed in athletes regularly subjecting the limb to high ground reaction forces (i.e., sprinters). Careful consideration should be given to the most appropriate assessment of stiffness on a team/individual basis.